Utilizing the One Stays Rest Stray Strategy to Teach Reading Comprehension - Sulaiman, Masagus; Larasati, Finza; Lestari, Ade Putri (CV. Doki Course and Training, 2024)
This study aimed at finding out whether or not one stays rest stray technique was effective to teach recount text reading comprehension achievements to the Eighth Grade Students of SMP Muhammadiyah 6 Palembang. This study used pre-experimental method. The samples of this study were 38 persons of the eighth-grade students of SMP Muhammadiyah 6 Palembang. The data was obtained from pretest and posttest and calculated by using t-test. The result showed t-obtained was 4.608, higher than the critical value of t-table was 1.689 at the significant level of p<0.05 for two tailed and degree of freedom (df) is 35 which means that Ho (Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. In conclusion, one stays rest stray technique was effective to teach recount text reading comprehension achievements to the Eighth Grade Students of SMP Muhammadiyah 6 Palembang